Preemptive treatment in the acute and early subacute phase of uncomplicated type B aortic dissections with poor prognosis factors - Sachs, Charlotte; Vecchini, Fabien; Corniquet, Marie; Bartoli, Michel; Barral, Pierre-Antoine; De Masi, Mariangela; Omnes, Virgile; Piquet, Philippe; Alsac, Jean-Marc; Gaudry, Marine (Frontiers in Cardiovascular Medicine, 2024)
Objective: The interest in thoracic endovascular repair (TEVAR) is growing in uncomplicated type B aortic dissections (TBAD) due to its favorable outcome regarding late morbidity and mortality. The aim of this study was to compare preemptive endovascular treatment and optimal medical treatment (OMT) versus OMT alone in patients presenting uncomplicated TBAD with predictors of aortic progression. Design: Retrospective multicenter study Methods: We analyzed patients with uncomplicated TBAD and risk factors of progression in two French academic centers. Late aortic events, postoperative complications, non-aortic events and radiologic aortic progression and remodeling were recorded and analyzed. Analysis was performed on an intention to treat basis. Results: Between 2011 and 2021, preemptive endovascular procedures were performed on 24 patients (group 1) and OMT alone was opted for 26 patients (group 2). After a mean follow-up 38.08 ± 24.53 months, late aortic events occurred in 20.83% patients from group 1 and 61.54% from group 2 (p< .001). There were no differences in postoperative events (p=1.00) and long-term non-aortic events (p=1.00). OMT patients had significantly more aneurysmal progression of the thoracic aorta (p< .001) and maximal aortic diameter (p< .001). Aortic remodeling was found in 91.67% of patients in group 1 and in 42.31% of patients in group 2 (p< .001). Conclusion: Preemptive treatment of uncomplicated TBAD with risk factors of progression reduces the risk of long-term aortic events. Over 60% of medically treated patients will require intervention during follow-up, with no benefit in terms of postoperative events. Even after surgical treatment, patients in the OMT group had significantly more aneurysmal progression, along with poorer aortic remodeling.